1971
DOI: 10.1192/bjp.119.549.213
|View full text |Cite
|
Sign up to set email alerts
|

A Study of Eye-Contact Changes in Depressed and Recovered Psychiatric Patients

Abstract: Eye-contact is a prominent Non-verbal cue in any Dyadic interaction and can be easily observed and measured. Argyle (1969) has postulated a relationship with Intimacy and Distance, Kendon (1967) described its expressive and regulatory function in conversation and Exline et al. (1965 and 1967) have related it to other variables, e.g. sex, dependency and affiliative needs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0
1

Year Published

1973
1973
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(17 citation statements)
references
References 7 publications
1
15
0
1
Order By: Relevance
“…The ability to jointly attend to or request an object is fundamental to social communication and provides the basis for affective sharing and intersubjectivity (Mundy, Kasari, & Sigman, 1992). Differences in eyecontact have been reported in other psychopathologies often comorbid with AN, including social anxiety disorder, where eye-tracking data show individuals avoid looking at the eyes (Weeks, Howell, & Goldin, 2013) and reductions in eye-contact are well documented in the clinical assessment of Major Depressive Disorder (Hinchliffe, Lancashire, & Roberts, 1971). In AN, one qualitative study found adolescents (n = 17) with AN report finding both giving and receiving eyecontact uncomfortable (Patel, Tchanturia, & Harrison, 2016) and one small study found that, independent of the observed body weight of actors in static images, 11 women with AN demonstrated significantly reduced gaze toward the face and eyes than 11 non-AN controls (Watson, Werling, Zucker, & Platt, 2010).…”
mentioning
confidence: 99%
“…The ability to jointly attend to or request an object is fundamental to social communication and provides the basis for affective sharing and intersubjectivity (Mundy, Kasari, & Sigman, 1992). Differences in eyecontact have been reported in other psychopathologies often comorbid with AN, including social anxiety disorder, where eye-tracking data show individuals avoid looking at the eyes (Weeks, Howell, & Goldin, 2013) and reductions in eye-contact are well documented in the clinical assessment of Major Depressive Disorder (Hinchliffe, Lancashire, & Roberts, 1971). In AN, one qualitative study found adolescents (n = 17) with AN report finding both giving and receiving eyecontact uncomfortable (Patel, Tchanturia, & Harrison, 2016) and one small study found that, independent of the observed body weight of actors in static images, 11 women with AN demonstrated significantly reduced gaze toward the face and eyes than 11 non-AN controls (Watson, Werling, Zucker, & Platt, 2010).…”
mentioning
confidence: 99%
“…Personality disorder-specific traits can be accurately perceived in thin slices of nonverbal behavior, and even psychopathology can be accurately perceived in both videos of targets as well as facial photographs (e.g., Fowler et al, 2009;Friedman et al, 2007;Holtzman, 2011). Both depression and anxiety can be accurately perceived in thin slices (see Harrigan et al, 2004;Hinchliffe et al, 1970Hinchliffe et al, , 1971Waxer, 1974Waxer, , 1976Yang et al, 2013). State and trait anxiety, for instance, are both detectable in thin slices, but in different channels.…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, continuous judgments of the severity of depression predicted scores on the Minnesota Multiphasic Personality Inventory Depression scale (see also Hinchliffe, Lancashire, & Roberts, 1970). Another study comparing participants who had recovered from depression to those who were still depressed found that those who were still depressed maintained less mutual eye gaze (Hinchliffe, Lancashire, & Roberts, 1971).…”
Section: Depressionmentioning
confidence: 99%
“…Das Blickniveau wird üblicher-weise in Prozent der Gesamtdauer angegeben. Die wenigen Untersuchungen, die unter Verwendung dieses Maßes an depressiven Patienten durchgeführt wurden (Rutter, Stephenson 1972, Hinchcliffe, Lancashire, Roberts 1973 Beiden Abbildungen ist das für die Gesprächsform »Interview« typische Grundmuster gemeinsam: Der Hauptanteil der Redezeit entfällt auf den Patienten (Interviewten), während der Interviewer nur durch kurze Fragen (Zustand 10) den Gesprächsfluß in Gang hält. Der Sprecherwechsel erfolgt über Pausen und nicht, wie z.…”
Section: Individuelles Blickniveauunclassified